Knowledge and attitude toward depression among healthcare professionals working in Ilu Aba Bor zone, Oromia regional state, Ethiopia, 2021: a cross sectional study - Alemayehu, Yadeta; Girma, Million; Bacha, Lemi; Boka, Kefale; Tarafa, Hunde (Frontiers in Psychiatry, 2023)
Background: Depression is the major mental disorder that frequently co-occurs with other physical illnesses, although its detection at primary health care is limited. Thus, the purpose of this study was to evaluate health professional's knowledge and attitude concerning depression and its related factors.Objective: To assess knowledge and attitude of health care professionals towards people with depression at different heath facilities of Ilu Aba Bor zone, Ethiopia, 2021 Methods: A cross sectional study was carried out involving 404 primary health care professionals using systematic random sampling technique in February 2021. Attitude was assessed by using depression attitude questionnaires. Epi-data version 3.1 and SPSS version 26 was used for data entry and analysis. P-values less than 0.05 were deemed statistically significant.Result: In the current study 30.4% (95% CI; 25.86, 34.94) of the respondents have inadequate knowledge, and 29.9% (95% CI; 25.4, 36.8) have negative attitude towards depression. A vast majority (77.7%) of Health Care Professionals have never received any kind of training on mental health. Accordingly, contact with person with mental illness and mental health training was significantly associated with inadequate knowledge. In addition perceived cause of depression and mental health training was significantly associated with negative attitude.According to this study the magnitude of inadequate knowledge and negative attitude in the diagnosis, and treatment of depression is comparably high. Therefore, the concern should be given to raise awareness, favor the attitude, and increase the rate at which depression cases are detected and treated in primary healthcare settings.